Любовь – основная тема романа Григориоса Ксенопулоса «Последние мечты» - Анохина, В.В.; Александрова, О.Н. (Культура народов Причерноморья, 2014)
В статье В.В. Анохиной и О.Н. Александровой «Любовь – основная тема романа
Григориоса Ксенопулоса «Последние мечты» определены основная тематика и проблемы,
затрагиваемые Григориосом Ксенопулосом в его романах. Материалом исследования стал роман
«Последние мечты». Также были рассмотрены роман «Старые Афины» и драма «Стелла Виоланди» в
контексте развития творчества писателя. В статье описывается своеобразие художественного мира
романов и сравнивается специфика их проблематики, образы, в которых воплощается тема любви. У статті визначені основна тематика і проблеми, втілені у романах Григоріоса Ксенопулоса.
Також були розглянуті роман «Старі Афіни» і драма «Стелла Віоланді» у контексті розвитку
творчості письменника. Показано, як вони відображені у творчості письменника. У статті
визначається своєрідність художнього світу романів і порівнюється специфіка їхньої проблематики,
образи, в якіх втілена любовна тема. The article defines the main topic and problems represented in the novels of Gregorios Xenopoulos.
«Last dreams». The material of the novel is the novel «Last dreams». And the novel «Old Athens» and drama «
Stella Violandi» were considered in the context of the writer's work. The article describes the singularity of the
artistic world of novels and compares the specificity of their problems, the images that embody the theme of love.
The main motives of the novels are formulated in the article. The novels of Gregorios Xenopoulos are the
example of his personal experience and the historical events reflected by the writer. The peculiarity of the real
world of Gregorios Xenopoulosis determined in the article. The particularities of the images of the author are
embedded in the synthesis of his philosophical, ethical and aesthetic values. The article compares the characters
from different novels, where the theme of love predominant and gives there views of some critics which help sinre
search of the writer's work. The article contains its topicality, the scientific novelty and the aim.